Biobased PLA/sugarcane bagasse fiber composites: Effect of fiber characteristics and interfacial adhesion on properties. (April 2021) - Bartos, András; Nagy, Kristóf; Anggono, Juliana; Antoni,; Purwaningsih, Hariyati; Móczó, János; Pukánszky, Béla
Abstract: PLA/sugarcane bagasse fiber composites were prepared by injection molding from two fractions of fibers with different fiber characteristics, which were determined before and after processing. Interfacial adhesion was modified by a maleated PLA coupling agent. The mechanical properties of the composites were characterized by tensile and impact testing, while local deformation processes by acoustic emission testing and microscopy. The results showed that considerable attrition takes place during melt processing in both the length and diameter of the fibers. The originally different batches of short and long fibers have similar dimensions after processing. Interfacial adhesion between PLA and bagasse is inherently good, thus coupling does not improve properties. Shear yielding and fiber fracture consume sufficiently energy to increase the impact resistance. Sugarcane bagasse fibers considerably increase the stiffness of PLA, result in almost constant tensile strength and increase impact resistance yielding a material with reasonable combination of properties for structural applications.